A multi-dimensional approach to thermal resilience for UK schools: quantifying cognitive, comfort and heat strain impacts due to overheating - Massimiliano Manfren; Patrick James; Michael Chater; Colin Jackson; Victoria Aragon; Azadeh Montazami; Stephanie Gauthier; Despoina Teli; Beverly Quinn; Karam Kalsi; Samuel Hough; Carys Thomas; et al. (Energy and Buildings, 2026)

Unprecedented Burning in Tropical Peatlands During the 20th Century Compared to the Previous Two Millennia - Yuwan Wang; Ted R. Feldpausch; Graeme T. Swindles; Patrick Moss; Hamish A. McGowan; Thomas G. Sim; Paul J. Morris; Adam Benfield; Colin Courtney‐Mustaphi; David Wahl; Encarni Montoya; Esther Githumbi; et al. (Global Change Biology, 2026)
Tropical peatland wildfire incidence has risen in recent decades, driven by drainage for land use and intensified by severe droughts with global climate change. These disturbances have altered vegetation structure, disrupted ecosystem functioning, and increased carbon emissions, particularly in Southeast Asia. However, the long‐term history and characteristics of wildfires in tropical peatlands remain largely unknown. Here, we compiled fifty‐eight macro‐charcoal records from peatlands across the tropics, ranging from lowland forested to montane peatlands, to assess millennia‐scale changes and controlling factors of tropical peatland burning. We divided the datasets into four main sub‐regions: Neotropical, Afrotropical, Indomalayan and Australasian ecoregions to explore regional variability. Tropical peatlands had high burning levels between 0 and 850 ce , followed by a relatively low and stable period until a marked increase during the 20th century. The general trend in tropical peatland burning follows changes in global temperature, and climate variables that control the length and severity of drought events have a notable influence on peat burning before 1900 ce . During the 20th century, regional differences were observed, with declining fire trends in the Neotropical and Afrotropical regions and increasing fire trends in the Indomalayan and Australasian regions. This difference is likely attributable to human activities, and such intervention is also evident in palm swamps and hardwood swamps under similar wet, weakly seasonal climates. With the increase in anthropogenic pressures on peatlands and greater climate variability, future wildfires in peatlands are likely to become more frequent and widespread across all tropical ecoregions. Conservation and sustainable land‐use practices could be used to mitigate and control peatland burning and protect these carbon‐rich sinks.

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Limited persistence of the heat-tolerant zooxanthella, Durusdinium trenchii, in corals transplanted to a barrier reef where it is rare among natal colonies - Kira E. Turnham; Allison M. Lewis; Dustin W. Kemp; Mark E. Warner; Drew F. Wham; Robin T. Smith; Kenneth Hoadley; Patrick L. Colin; Yimnang Golbuu; Todd C. LaJeunesse (Coral Reefs, 2025)

Complex landscape, instream and anthropogenic environmental features drive genetic and morphological structuring amongst brown trout (Salmo trutta) populations in a dendritic river system - Jessica R. Rodger; Hannele M. Honkanen; Caroline R. Bradley; Patrick Boylan; Paulo A. Prodöhl; Colin E. Adams (Evolutionary Ecology, 2025)
Untangling the patterns and proximate drivers of intraspecific genetic and phenotypic structuring informs our understanding of the evolutionary processes shaping diversity. This study investigated morphological and genetic structuring of brown trout ( Salmo trutta L.) populations across varying spatial scales in a single, complex, dendritic river catchment and examined the potential natural and anthropogenic environmental features driving this structuring. Morphometric and hierarchical genetic structuring analyses of fish from 22 sampling sites in the River Foyle catchment, Ireland (~ 4500km 2 ) identified 19 morphologically distinct groups and 15 genetically distinct populations, separated by river distances ranging from 0.4 km to 188 km. Isolation by Distance was the main factor shaping both genetic and morphological divergence, indicating that strong philopatry is one of the major drivers of the observed population structuring in this system. However, both natural and anthropogenic environmental variables also explained pairwise genetic and morphological differences between sampling sites. Thus, the pairwise differences in the area of woodland in the upstream catchment, water phosphorus concentration, biological oxygen demand, catchment slope, urban area in upstream catchment, altitude, site specific percentage of canopy cover and dissolved oxygen concentration in the river channel were correlated with genetic divergence. The pairwise differences in the concentration of suspended solids, the extent of bankside overhang, the composition of bedrock, boulder and cobble substrates, watercourse width, catchment slope and site altitude were correlated with between-site morphological differences. We hypothesise that local differential selection pressures comprising both natural environmental variation and variation resulting from anthropogenic effects, in combination with strong philopatry and random genetic processes drive the clearly defined genetic and phenotypic patterns described here.

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

The Visual Monitoring Camera (VMC) on Mars Express: A new science instrument made from an old webcam orbiting Mars - Jorge Hernández-Bernal; Alejandro Cardesín-Moinelo; Ricardo Hueso; Eleni Ravanis; Abel Burgos-Sierra; Simon Wood; Marc Costa-Sitja; Alfredo Escalante; Emmanuel Grotheer; Julia Marín-Yaseli de la Parra; Donald Merrit; Miguel Almeida; et al. (Planetary and Space Science, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Pathways from research to sustainable development: Insights from ten research projects in sustainability and resilience - Anna Scaini; Joseph Mulligan; Håkan Berg; Albert Brangarí; Vera Bukachi; Sebastian Carenzo; Da Chau Thi; Colin Courtney-Mustaphi; Anneli Ekblom; Hanne Fjelde; Mathias Fridahl; Anders Hansson; et al. (Ambio, 2024)
Drawing on collective experience from ten collaborative research projects focused on the Global South, we identify three major challenges that impede the translation of research on sustainability and resilience into better-informed choices by individuals and policy-makers that in turn can support transformation to a sustainable future. The three challenges comprise: (i) converting knowledge produced during research projects into successful knowledge application; (ii) scaling up knowledge in time when research projects are short-term and potential impacts are long-term; and (iii) scaling up knowledge across space, from local research sites to larger-scale or even global impact. Some potential pathways for funding agencies to overcome these challenges include providing targeted prolonged funding for dissemination and outreach, and facilitating collaboration and coordination across different sites, research teams, and partner organizations. By systematically documenting these challenges, we hope to pave the way for further innovations in the research cycle.

Migration patterns and navigation cues of Atlantic salmon post‐smolts migrating from 12 rivers through the coastal zones around the Irish Sea - Jessie Lilly; Hannele H. Honkanen; Jessica R. Rodger; Diego del Villar; Patrick Boylan; Amy Green; Diego Pereiro; Lorna Wilkie; Richard Kennedy; Andrea Barkley; Robert Rosell; Niall Ó. Maoiléidigh; et al. (Journal of Fish Biology, 2024)
The freshwater phase of the first seaward migration of juvenile Atlantic salmon ( Salmo salar ) is relatively well understood when compared with our understanding of the marine phase of their migration. In 2021, 1008 wild and 60 ranched Atlantic salmon smolts were tagged with acoustic transmitters in 12 rivers in England, Scotland, Northern Ireland and Ireland. Large marine receiver arrays were deployed in the Irish Sea at two locations: at the transition of the Irish Sea into the North Atlantic between Ireland and Scotland, and between southern Scotland and Northern Ireland, to examine the early phase of the marine migration of Atlantic salmon smolts. After leaving their natal rivers' post‐smolt migration through the Irish Sea was rapid with minimum speeds ranging from 14.03 to 38.56 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal river, to 9.69–39.94 km.day −1 for Atlantic salmon smolts that entered the Irish Sea directly from their natal estuary. Population minimum migration success through the study area was strongly correlated with the distance of travel, populations further away from the point of entry to the open North Atlantic exhibited lower migration success. Post‐smolts from different populations experienced different water temperatures on entering the North Atlantic. This was largely driven by the timing of their migration and may have significant consequences for feeding and ultimately survivorship. The influence of water currents on post‐smolt movement was investigated using data from previously constructed numerical hydrodynamic models. Modeled water current data in the northern Irish Sea showed that post‐smolts had a strong preference for migrating when the current direction was at around 283° (west‐north‐west) but did not migrate when exposed to strong currents in other directions. This is the most favorable direction for onward passage from the Irish Sea to the continental shelf edge current, a known accumulation point for migrating post‐smolts. These results strongly indicate that post‐smolts migrating through the coastal marine environment are: (1) not simply migrating by current following (2) engage in active directional swimming (3) have an intrinsic sense of their migration direction and (4) can use cues other than water current direction to orientate during this part of their migration.

Guitarfishes are plucked: Undermanaged in global fisheries despite declining populations and high volume of unreported international trade - C. Samantha Sherman; Colin A. Simpfendorfer; Alifa B. Haque; Eric D. Digel; Patrick Zubick; Jonathan Eged; Jay H. Matsushiba; Glenn Sant; Nicholas K. Dulvy (Marine Policy, 2023)

Spatial and temporal variations of seabed sediment characteristics in the inner Louisiana shelf - Wenqiang Zhang; Kehui Xu; Colin Herke; Omar Alawneh; Navid Jafari; Kanchan Maiti; Patrick O. Clower; Cassandra N. Glaspie; Jillian C. Tupitza; Z. George Xue (Marine Geology, 2023)

Unraveling the climate control on debris-free glacier evolution in the Everest region (Nepal, central Himalaya) during the Holocene - Vincent Jomelli; Patrick Wagnon; Didier Swingedouw; Joanna Charton; Régis Braucher; Adèle Hue; Fanny Brun; Christophe Colin; Stephanie Gairoard; Dibas Shrestha; Georges Aumaître; Karim Keddadouche; et al. (Quaternary Science Reviews, 2023)

Nearly five-year continuous atmospheric measurements of black carbon over a suburban area in central France - El. Mehdi EL. Baramoussi; Yangang Ren; Chaoyang Xue; Ibrahim Ouchen; Véronique Daële; Patrick Mercier; Christophe Chalumeau; Frédéric L.E. Fur; Patrice Colin; Abderrazak Yahyaoui; Oliver Favez; Abdelwahid Mellouki (Science of The Total Environment, 2023)

M‐Risk : A framework for assessing global fisheries management efficacy of sharks, rays and chimaeras - C. Samantha Sherman; Glenn Sant; Colin A. Simpfendorfer; Eric D. Digel; Patrick Zubick; Grant Johnson; Michael Usher; Nicholas K. Dulvy (Fish and Fisheries, 2022)
Fisheries management is essential to guarantee sustainable capture of target species and avoid undesirable declines of incidentally captured species. A key challenge is halting and reversing declines of shark and ray species, and specifically assessing the degree to which management is sufficient to avoid declines in relatively data‐poor fisheries. While ecological risk analyses focus on intrinsic ‘productivity’ and extrinsic ‘susceptibility’, one would ideally consider the influence of ‘fisheries management’. Currently, there is no single management evaluation that can be applied to a combination of fishery types at the scale of individual country or Regional Fisheries Management Organizations (RFMOs). Here, we outline a management‐risk (M‐Risk) framework for sharks, rays and chimaeras used to evaluate species' risk of overfishing resulting from ineffective management. We illustrate our approach with application to one country (Ecuador) and RFMO (Inter‐American Tropical Tuna Commission) and illustrate the variation in scores among species. We found that while both management units assessed had similar overall scores, the scores for individual attributes varied. Ecuador scored higher in reporting‐related attributes, while the IATTC scored higher in attributes related to data collection and use. We evaluated whether the management of individual species was sufficient for their relative sensitivity by combining the management‐risk score for each species with their intrinsic sensitivity to determine a final M‐Risk score. This framework can be applied to determine which species face the greatest risk of overfishing and be used by fisheries managers to identify effective management policies by replicating regulations from countries with lower risk scores.

Genomics reveal population structure, evolutionary history, and signatures of selection in the northern bottlenose whale, Hyperoodon ampullatus - Evelien de Greef; Anthony L. Einfeldt; Patrick J. O. Miller; Steven H. Ferguson; Colin J. Garroway; Kyle J. Lefort; Ian G. Paterson; Paul Bentzen; Laura J. Feyrer (Molecular Ecology, 2022)
Information on wildlife population structure, demographic history, and adaptations are fundamental to understanding species evolution and informing conservation strategies. To study this ecological context for a cetacean of conservation concern, we conducted the first genomic assessment of the northern bottlenose whale, Hyperoodon ampullatus , using whole‐genome resequencing data ( n = 37) from five regions across the North Atlantic Ocean. We found a range‐wide pattern of isolation‐by‐distance with a genetic subdivision distinguishing three subgroups: the Scotian Shelf, western North Atlantic, and Jan Mayen regions. Signals of elevated levels of inbreeding in the Endangered Scotian Shelf population indicate this population may be more vulnerable than the other two subgroups. In addition to signatures of inbreeding, evidence of local adaptation in the Scotian Shelf was detected across the genome. We found a long‐term decline in effective population size for the species, which poses risks to their genetic diversity and may be exacerbated by the isolating effects of population subdivision. Protecting important habitat and migratory corridors should be prioritized to rebuild population sizes that were diminished by commercial whaling, strengthen gene flow, and ensure animals can move across regions in response to environmental changes.

A possible role for river restoration enhancing biodiversity through interaction with wildfire - Brittany E. Pugh; Megan Colley; Stephen J. Dugdale; Patrick Edwards; Rebecca Flitcroft; Andrés Holz; Matthew Johnson; Michela Mariani; Mickey Means‐Brous; Kate Meyer; Kevan B. Moffett; Lisa Renan; et al. (Global Ecology and Biogeography, 2022)
Background Historically, wildfire regimes produced important landscape‐scale disturbances in many regions globally. The “pyrodiversity begets biodiversity” hypothesis suggests that wildfires that generate temporally and spatially heterogeneous mosaics of wildfire severity and post‐burn recovery enhance biodiversity at landscape scales. However, river management has often led to channel incision that disconnects rivers from their floodplains, desiccating floodplain habitats and depleting groundwater. In conjunction with predicted increases in frequency, intensity and extent of wildfires under climate change, this increases the likelihood of deep, uniform burns that reduce biodiversity. Predicted synergy of river restoration and biodiversity increase Recent focus on floodplain re‐wetting and restoration of successional floodplain habitat mosaics, developed for river management and flood prevention, could reduce wildfire intensity in restored floodplains and make the burns less uniform, increasing climate‐change resilience; an important synergy. According to theory, this would also enhance biodiversity. However, this possibility is yet to be tested empirically. We suggest potential research avenues. Illustration and future directions We illustrate the interaction between wildfire and river restoration using a restoration project in Oregon, USA. A project to reconnect the South Fork McKenzie River and its floodplain suffered a major burn (“Holiday Farm” wildfire, 2020), offering a rare opportunity to study the interaction between this type of river restoration and wildfire; specifically, the predicted increases in pyrodiversity and biodiversity. Given the importance of river and wetland ecosystems for biodiversity globally, a research priority should be to increase our understanding of potential mechanisms for a “triple win” of flood reduction, wildfire alleviation and biodiversity promotion.

Environmental management systems in the architectural, engineering and construction sectors: a roadmap to aid the delivery of the sustainable development goals - Rosemary Horry; Colin A. Booth; Abdul–Majeed Mahamadu; Patrick Manu; Panos Georgakis (Environment, Development and Sustainability, 2022)
Realisation of the sustainable development goals (SDGs) will provide improvements to people's lives and longevity of the planet. The architectural, engineering and construction (AEC) sectors have a potentially huge role in aiding the delivery of many SDGs; however, there appears to be a lack of research into the engagement within this sector. The leading environmental management system (EMS), ISO 14001, can enable organisations in the AEC sectors to improve their business operations, whilst minimising their impacts on the environment and improving society. Therefore, the study sets out to use institutional theory to determine the usefulness of ISO 14001 as a tool within the AEC sector and to demonstrate how the organisational benefits could facilitate the delivery of the SDGs. A stepwise PRISMA review process facilitated the compiling of academic articles and professional reports ( n = 44), which enabled the creation of an inventory of the perceived benefits ( n = 85) and the recognised barriers ( n = 63) to implementing ISO 14001 across the AEC sectors. These barriers and benefits were confirmed by environmental practitioners as being relevant to the incorporation of an EMS. The most widely reported benefits within the AEC sectors were improving environmental performance and compliance with legislation. Lack of government pressure and lack of expertise were the most widely reported barriers, followed by cost to AEC organisations utilising an EMS. Following on from this inventory of benefits, it was possible to develop of a conceptual roadmap, which illustrates where linkages exist with the SDGs. SDG 4, 8, 12 and 13 are shown as exhibiting the most associations with the benefits. This roadmap was reviewed by AEC sector professionals who confirmed its usefulness. Therefore, it is surmised that the roadmap could aid strategic organisational sustainable planning or for organisations to demonstrate the delivery of their corporate social responsibilities.

Can I afford to publish? A dilemma for African scholars - Addisu Mekonnen; Colleen Downs; Edu O. Effiom; Mohamed Kibaja; Michael J. Lawes; Patrick Omeja; Fanomezana M. Ratsoavina; Onja Razafindratsima; Dipto Sarkar; Nils Chr. Stenseth; Colin A. Chapman (Ecology Letters, 2022)
With open‐access publishing authors often pay an article processing charge and subsequently their article is freely available online. These charges are beyond the reach of most African academics. Thus, the trend towards open‐access publishing will shift the business model from a pay‐wall model, where access to literature is limited, to a pay‐to‐publish one, where African scholars cannot afford to publish. We explore the costs of publishing and the ability of African scholars to afford to publish via open access in top journals. Three‐quarters of the 40 top ecology journals required payment for open‐access publishing (average cost $3150). Paying such fees is a hardship for African scholars as grant funding is not available and it is not feasible to pay the fees themselves as salaries are low. We encourage funders and publishers to facilitate an equitable publishing model that allows African scholars to make their research available through open‐access publishing.

Extreme bill dimorphism leads to different but overlapping isotopic niches and similar trophic positions in sexes of the charismatic extinct huia - Barbara M. Tomotani; Rodrigo B. Salvador; Amandine J. M. Sabadel; Colin M. Miskelly; Julie C. S. Brown; Josette Delgado; Patrick Boussès; Yves Cherel; Susan M. Waugh; Sarah J. Bury (Oecologia, 2022)
The New Zealand huia ( Heteralocha acutirostris ) had the most extreme bill sexual dimorphism among modern birds. Given the quick extinction of the species, the cause of the dimorphism could only be hypothesised to reflect different trophic niches and reduce male/female competition. We tested that hypothesis by combining museum specimens, geometric morphometrics, and isotopic analyses. We used geometric morphometrics to describe bill shape; measured bulk ( δ 15 N bulk ) and ( δ 13 C bulk ) values from feather as proxies of the birds’ foraging habitat and diet; and compared compound-specific stable isotopes analyses (CSIA) of nitrogen in amino acids ( δ 15 N AA ) in male–female pairs to estimate their trophic position. Sexes had significantly different, but overlapping feather δ 15 N bulk and δ 13 C bulk values, but δ 15 N AA indicated identical trophic positions and δ 15 N bulk was not related to bill shape. Trophic position was less variable among females, consistent with a specialised foraging behaviour and, thus, supporting a partial male/female foraging segregation.

A Critical Review of Current Imaging Techniques to Investigate Water Transfers in Wood and Biosourced Materials - Dang Mao Nguyen; Giana Almeida; Thi Mai Loan Nguyen; Jing Zhang; Pin Lu; Julien Colin; Patrick Perré (Transport in Porous Media, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

A Decade of Monitoring an Indo-Pacific Grouper Spawning Aggregation: Benefits of Protection and Importance of Survey Design - Yvonne Sadovy de Mitcheson; Patrick L. Colin; Steven J. Lindfield; Asap Bukurrou (Frontiers in Marine Science, 2020)

Measuring Temperature in Coral Reef Environments: Experience, Lessons, and Results from Palau - Patrick L. Colin; T. M. Shaun Johnston (Journal of Marine Science and Engineering, 2020)
Sea surface temperature, determined remotely by satellite (SSST), measures only the thin “skin” of the ocean but is widely used to quantify the thermal regimes on coral reefs across the globe. In situ measurements of temperature complements global satellite sea surface temperature with more accurate measurements at specific locations/depths on reefs and more detailed data. In 1999, an in situ temperature-monitoring network was started in the Republic of Palau after the 1998 coral bleaching event. Over two decades the network has grown to 70+ stations and 150+ instruments covering a 700 km wide geographic swath of the western Pacific dominated by multiple oceanic currents. The specific instruments used, depths, sampling intervals, precision, and accuracy are considered with two goals: to provide comprehensive general coverage to inform global considerations of temperature patterns/changes and to document the thermal dynamics of many specific habitats found within a highly diverse tropical marine location. Short-term in situ temperature monitoring may not capture broad patterns, particularly with regard to El Niño/La Niña cycles that produce extreme differences. Sampling over two decades has documented large T signals often invisible to SSST from (1) internal waves on time scales of minutes to hours, (2) El Niño on time scales of weeks to years, and (3) decadal-scale trends of +0.2 °C per decade. Network data have been used to create a regression model with SSST and sea surface height (SSH) capable of predicting depth-varying thermal stress. The large temporal, horizontal, and vertical variability noted by the network has further implications for thermal stress on the reef. There is a dearth of definitive thermal information for most coral reef habitats, which undermines the ability to interpret biological events from the most basic physical perspective.

Fruit Selectivity in Anthropoid Primates: Size Matters - Kim Valenta; David J. Daegling; Omer Nevo; Justin Ledogar; Dipto Sarkar; Urs Kalbitzer; Sarah Bortolamiol; Patrick Omeja; Colin A. Chapman; Manfred Ayasse; Richard Kay; Blythe Williams (International Journal of Primatology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Ngaraard Pinnacle, Palau: An Undersea “Island” in the Flow - Patrick Colin; Shaun Johnston; Jennifer MacKinnon; Celia Ou; Daniel Rudnick; Eric Terrill; Steven Lindfield; Heidi Batchelor (Oceanography, 2019)

Tropical Western Pacific Thermal Structure and its Relationship to Ocean Surface Variables: A Numerical State Estimate and Forereef Temperature Records - Travis Schramek; Bruce Cornuelle; Ganesh Gopalakrishnan; Patrick Colin; Sonia Rowley; Mark Merrifield; Eric Terrill (Oceanography, 2019)

Energy and Momentum Lost to Wake Eddies and Lee Waves Generated by the North Equatorial Current and Tidal Flows at Peleliu, Palau - Shaun Johnston; Jennifer MacKinnon; Patrick Colin; Patrick Haley; Pierre Lermusiaux; Andrew Lucas; Mark Merrifield; Sophia Merrifield; Chris Mirabito; Jonathan Nash; Celia Ou; Mika Siegelman; et al. (Oceanography, 2019)

Island Wakes Observed from High-Frequency Current Mapping Radar - Sophia Merrifield; Patrick Colin; Thomas Cook; Carlos Garcia-Moreno; Jennifer MacKinnon; Mark Otero; Travis Schramek; Mika Siegelman; Harper Simmons; Eric Terrill (Oceanography, 2019)

Dynamical Downscaling of Equatorial Flow Response to Palau - Harper Simmons; Brian Powell; Sophia Merrifield; Sarah Zedler; Patrick Colin (Oceanography, 2019)

Typhoon-Forced Waves Around a Western Pacific Island Nation - Sophia Merrifield; Travis Schramek; Sean Celona; Ana Beatriz Villas Bôas; Patrick Colin; Eric Terrill (Oceanography, 2019)

The End of an El Niño: A View from Palau - Martha Schönau; Hemantha Wijesekera; William Teague; Patrick Colin; Ganesh Gopalakrishnan; Daniel Rudnick; Bruce Cornuelle; Zachariah Hallock; David Wang (Oceanography, 2019)

Nonlinear Short-Term Upper Ocean Circulation Variability in the Tropical Western Pacific - Bo Qiu; Shuiming Chen; Brian Powell; Patrick Colin; Daniel Rudnick; Martha Schönau (Oceanography, 2019)

FLEAT: A Multiscale Observational and Modeling Program to Understand How Topography Affects Flows in the Western North Pacific - Shaun Johnston; Martha Schönau; Terri Paluszkiewicz; Jennifer MacKinnon; Brian Arbic; Patrick Colin; Matthew Alford; Magdalena Andres; Luca Centurioni; Hans Graber; Karl Helfrich; Verena Hormann; et al. (Oceanography, 2019)

Correction to: The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Arthur L. Beaudet; Steve D. M. Brown; Mary E. Dickinson; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Conservation Genetics, 2019)

Comparative population genomics reveals key barriers to dispersal in Southern Ocean penguins - Gemma V. Clucas; Jane L. Younger; Damian Kao; Louise Emmerson; Colin Southwell; Barbara Wienecke; Alex D. Rogers; Charles‐André Bost; Gary D. Miller; Michael J. Polito; Patrick Lelliott; Jonathan Handley; et al. (Molecular Ecology, 2018)
The mechanisms that determine patterns of species dispersal are important factors in the production and maintenance of biodiversity. Understanding these mechanisms helps to forecast the responses of species to environmental change. Here, we used a comparative framework and genomewide data obtained through RAD ‐Seq to compare the patterns of connectivity among breeding colonies for five penguin species with shared ancestry, overlapping distributions and differing ecological niches, allowing an examination of the intrinsic and extrinsic barriers governing dispersal patterns. Our findings show that at‐sea range and oceanography underlie patterns of dispersal in these penguins. The pelagic niche of emperor ( Aptenodytes forsteri ), king ( A. patagonicus ), Adélie ( Pygoscelis adeliae ) and chinstrap ( P. antarctica ) penguins facilitates gene flow over thousands of kilometres. In contrast, the coastal niche of gentoo penguins ( P. papua ) limits dispersal, resulting in population divergences. Oceanographic fronts also act as dispersal barriers to some extent. We recommend that forecasts of extinction risk incorporate dispersal and that management units are defined by at‐sea range and oceanography in species lacking genetic data.

Gauging support for macroecological patterns in helminth parasites - Tad A. Dallas; A. Alonso Aguirre; Sarah Budischak; Colin Carlson; Vanessa Ezenwa; Barbara Han; Shan Huang; Patrick R. Stephens (Global Ecology and Biogeography, 2018)
Aim To explore spatial patterns of helminth parasite diversity, and to investigate three main macroecological patterns – (a) latitude–diversity relationships, (b) positive scaling between parasite and host diversity, and (c) species–area relationships – using a largely underutilized global database of helminth parasite occurrence records. Location Global. Methods We examined the London Natural History Museum’s collection of helminth parasite occurrence records, consisting of over 18,000 unique host species and 27,000 unique helminth parasite species distributed across over 350 distinct terrestrial and aquatic localities. Results We find support for latitudinal gradients in parasite diversity and a strong relationship between host and parasite diversity at the global scale. Helminth species diversity–area relationships were not detectable as a function of host body mass, but larger geographic areas supported higher parasite richness, potentially mediated through higher host richness. Main conclusions Our findings indicate that helminth parasites may obey some of the macroecological relationships found in free‐living species, suggesting that parasites may offer further support for the generality of these patterns, while offering interesting counterexamples for others. We conclude with a discussion of future directions and potential challenges in the newly emerging macroecology of infectious disease.

Targeting therapeutics to endothelium: are we there yet? - Raisa Yu. Kiseleva; Patrick M. Glassman; Colin F. Greineder; Elizabeth D. Hood; Vladimir V. Shuvaev; Vladimir R. Muzykantov (Drug Delivery and Translational Research, 2018)

The International Mouse Phenotyping Consortium (IMPC): a functional catalogue of the mammalian genome that informs conservation - Violeta Muñoz-Fuentes; Pilar Cacheiro; Terrence F. Meehan; Juan Antonio Aguilar-Pimentel; Steve D. M. Brown; Ann M. Flenniken; Paul Flicek; Antonella Galli; Hamed Haseli Mashhadi; Martin Hrabě de Angelis; Jong Kyoung Kim; K. C. Kent Lloyd; et al. (Conservation Genetics, 2018)
The International Mouse Phenotyping Consortium (IMPC) is building a catalogue of mammalian gene function by producing and phenotyping a knockout mouse line for every protein-coding gene. To date, the IMPC has generated and characterised 5186 mutant lines. One-third of the lines have been found to be non-viable and over 300 new mouse models of human disease have been identified thus far. While current bioinformatics efforts are focused on translating results to better understand human disease processes, IMPC data also aids understanding genetic function and processes in other species. Here we show, using gorilla genomic data, how genes essential to development in mice can be used to help assess the potentially deleterious impact of gene variants in other species. This type of analyses could be used to select optimal breeders in endangered species to maintain or increase fitness and avoid variants associated to impaired-health phenotypes or loss-of-function mutations in genes of critical importance. We also show, using selected examples from various mammal species, how IMPC data can aid in the identification of candidate genes for studying a condition of interest, deliver information about the mechanisms involved, or support predictions for the function of genes that may play a role in adaptation. With genotyping costs decreasing and the continued improvements of bioinformatics tools, the analyses we demonstrate can be routinely applied.

Ocean Warming and the Reefs of Palau - Patrick Colin (Oceanography, 2018)

Primate population dynamics: variation in abundance over space and time - Colin A. Chapman; Sarah Bortolamiol; Ikki Matsuda; Patrick A. Omeja; Fernanda P. Paim; Rafael Reyna-Hurtado; Raja Sengupta; Kim Valenta (Biodiversity and Conservation, 2018)

Park isolation in anthropogenic landscapes: land change and livelihoods at park boundaries in the African Albertine Rift - Jonathan Salerno; Colin A. Chapman; Jeremy E. Diem; Nicholas Dowhaniuk; Abraham Goldman; Catrina A. MacKenzie; Patrick Aria Omeja; Michael W. Palace; Rafael Reyna-Hurtado; Sadie J. Ryan; Joel Hartter (Regional Environmental Change, 2018)

Fruit defence syndromes: the independent evolution of mechanical and chemical defences - Omer Nevo; Kim Valenta; Alex G. Tevlin; Patrick Omeja; Sarah A. Styler; Derek J. Jackson; Colin A. Chapman; Manfred Ayasse (Evolutionary Ecology, 2017)

Transforming conservation science and practice for a postnormal world - Matthew J. Colloff; Sandra Lavorel; Lorrae E. van Kerkhoff; Carina A. Wyborn; Ioan Fazey; Russell Gorddard; Georgina M. Mace; Wendy B. Foden; Michael Dunlop; I. Colin Prentice; John Crowley; Paul Leadley; et al. (Conservation Biology, 2017)
We examine issues to consider when reframing conservation science and practice in the context of global change. New framings of the links between ecosystems and society are emerging that are changing peoples’ values and expectations of nature, resulting in plural perspectives on conservation. Reframing conservation for global change can thus be regarded as a stage in the evolving relationship between people and nature rather than some recent trend. New models of how conservation links with transformative adaptation include how decision contexts for conservation can be reframed and integrated with an adaptation pathways approach to create new options for global‐change‐ready conservation. New relationships for conservation science and governance include coproduction of knowledge that supports social learning. New processes for implementing adaptation for conservation outcomes include deliberate practices used to develop new strategies, shift world views, work with conflict, address power and intergenerational equity in decisions, and build consciousness and creativity that empower agents to act. We argue that reframing conservation for global change requires scientists and practitioners to implement approaches unconstrained by discipline and sectoral boundaries, geopolitical polarities, or technical problematization. We consider a stronger focus on inclusive creation of knowledge and the interaction of this knowledge with societal values and rules is likely to result in conservation science and practice that meets the challenges of a postnormal world.

Cis ‐regulatory evolution in a wild primate: Infection‐associated genetic variation drives differential expression of MHC ‐ DQA 1 in vitro - Noah D. Simons; Geeta N. Eick; Maria J. Ruiz‐Lopez; Patrick A. Omeja; Colin A. Chapman; Tony L. Goldberg; Nelson Ting; Kirstin N. Sterner (Molecular Ecology, 2017)
Few studies have combined genetic association analyses with functional characterization of infection‐associated SNP s in natural populations of nonhuman primates. Here, we investigate the relationship between host genetic variation, parasitism and natural selection in a population of red colobus ( Procolobus rufomitratus tephrosceles ) in Kibale National Park, Uganda. We collected parasitological, cellular and genomic data to test the following hypotheses: (i) MHC ‐ DQA 1 regulatory genetic variation is associated with control of whipworm ( Trichuris ) infection in a natural population of red colobus; (ii) infection‐associated SNP s are functional in driving differential gene expression in vitro; and (iii) balancing selection has shaped patterns of variation in the MHC ‐ DQA 1 promoter. We identified two SNP s in the MHC ‐ DQA 1 promoter, both in transcription factor binding sites, and both of which are associated with decreased control of Trichuris infection. We characterized the function of both SNP s by testing differences in gene expression between the two alleles of each SNP in two mammalian cell lines. Alleles of one of the SNP s drove differential gene expression in both cell lines, while the other SNP drove differences in expression in one of the cell lines. Additionally, we found evidence of balancing selection acting on the MHC ‐ DQA 1 promoter, including extensive trans‐species polymorphisms between red colobus and other primates, and an excess of intermediate‐frequency alleles relative to genome‐wide, coding and noncoding RAD seq data. Our data suggest that balancing selection provides adaptive regulatory flexibility that outweighs the consequences of increased parasite infection intensity in heterozygotes.

Project Recover: Extending the Applications of Unmanned Platforms and Autonomy to Support Underwater MIA Searches - Eric Terrill; Mark Moline; Patrick Scannon; Eric Gallimore; Travis Shramek; Andy Nager; Robert Hess; Megan Cimino; Patrick Colin; Andrew Pietruszka; Mark Anderson (Oceanography, 2017)

Consistency in coral skeletal amino acid composition offshore of Palau in the western Pacific warm pool indicates no impact of decadal variability in nitricline depth on primary productivity - Branwen Williams; Benoit Thibodeau; Yoshito Chikaraishi; Naohiko Ohkouchi; Andrew Walnum; Andréa G. Grottoli; Patrick L. Colin (Limnology and Oceanography, 2017)
The depth of the thermocline and associated nitricline in the western Pacific warm pool (WPWP) vary over time in response to changes in larger ocean‐atmosphere climate patterns. A shoaling of the nitricline in the WPWP brings nitrate‐rich seawater ( > 4 μ mol kg −1 ) above the base of the euphotic zone, stimulating primary productivity. Here, we test if decadal variability in the nitricline depth is driving changes in regional primary productivity and source nitrate dynamics. We use the nitrogen isotopic composition (δ 15 N) of amino acids in the skeleton of a proteinaceous coral collected from the base of the euphotic zone in the WPWP. In proteinaceous corals, as in most organic life, the δ 15 N of phenylalanine matches that of the ambient nitrate while the δ 15 N of trophic amino acids reflect subsequent trophic transfer of the nitrogen prior to incorporation into the coral's food, suspended particulate organic matter. Consistency of the trophic position of the coral calculated from the δ 15 N composition of the coral skeletal amino acids over its 56 yr lifespan suggest that decadal variability in nitricline depth and subsequent shifts in nitrate availability to the euphotic zone have not impacted primary productivity offshore of Palau in the WPWP. This is important when considering the current external forcing of Pacific Ocean climate patterns and the resulting impacts on the global carbon cycle in the Palau region of the WPWP.

What have we learnt from palaeoclimate simulations? - Sandy P. Harrison; Patrick J. Bartlein; I. Colin Prentice (Journal of Quaternary Science, 2016)
There has been a gradual evolution in the way that palaeoclimate modelling and palaeoenvironmental data are used together to understand how the Earth System works, from an initial and largely descriptive phase through explicit hypothesis testing to diagnosis of underlying mechanisms. Analyses of past climate states are now regarded as integral to the evaluation of climate models, and have become part of the toolkit used to assess the likely realism of future projections. Palaeoclimate assessment has demonstrated that changes in large‐scale features of climate that are governed by the energy and water balance show consistent responses to changes in forcing in different climate states, and these consistent responses are reproduced by climate models. However, state‐of‐the‐art models are still largely unable to reproduce observed changes in climate at a regional scale reliably. While palaeoclimate analyses of state‐of‐the‐art climate models suggest an urgent need for model improvement, much work is also needed on extending and improving palaeoclimate reconstructions and quantifying and reducing both numerical and interpretative uncertainties.

Remembering Jerry Lwanga: A Perspective from His Colleagues - Tony L. Goldberg; Samuel Angedakin; Gilbert M. Isabirye Basuta; Michelle Brown; Thomas M. Butynski; Colin A. Chapman; Lauren Chapman; Sholly Gunter; Innocent Kato; Jean-Michel Krief; Sabrina Krief; Joanna E. Lambert; et al. (International Journal of Primatology, 2016)

Rapid identification of major histocompatibility complex class I haplotypes using deep sequencing in an endangered Old World monkey - Noah D. Simons; Maria Jose Ruiz-Lopez; Colin A. Chapman; Tony L. Goldberg; Julie A. Karl; Roger W. Wiseman; Patrick S. Bohn; David H. O’Connor; Nelson Ting (Conservation Genetics Resources, 2016)

The effect of recreational SCUBA divers on the structural complexity and benthic assemblage of a Caribbean coral reef - Patrick J. Lyons; Enrique Arboleda; Cassandra E. Benkwitt; Brooke Davis; Molly Gleason; Colin Howe; Jennifer Mathe; Julia Middleton; Nicole Sikowitz; Lucien Untersteggaber; Stephanie Villalobos (Biodiversity and Conservation, 2015)

Antibiotic Resistance Among Cultured Bacterial Isolates from Bioethanol Fermentation Facilities Across the United States - Colin A. Murphree; E. Patrick Heist; Luke A. Moe (Current Microbiology, 2014)

Case–control association study of polymorphisms in the voltage-gated sodium channel genes SCN1A, SCN2A, SCN3A, SCN1B, and SCN2B and epilepsy - Larry Baum; Batoul Sadat Haerian; Ho-Keung Ng; Virginia C. N. Wong; Ping Wing Ng; Colin H. T. Lui; Ngai Chuen Sin; Chunbo Zhang; Brian Tomlinson; Gary Wing-Kin Wong; Hui Jan Tan; Azman Ali Raymond; et al. (Human Genetics, 2014)

Erratum to: EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

Are Primates Ecosystem Engineers? - Colin A. Chapman; Tyler R. Bonnell; Jan F. Gogarten; Joanna E. Lambert; Patrick A. Omeja; Dennis Twinomugisha; Michael D. Wasserman; Jessica M. Rothman (International Journal of Primatology, 2013)

Stimulant effects of adenosine antagonists on operant behavior: differential actions of selective A2A and A1 antagonists - Patrick A. Randall; Eric J. Nunes; Simone L. Janniere; Colin M. Stopper; Andrew M. Farrar; Thomas N. Sager; Younis Baqi; Jörg Hockemeyer; Christa E. Müller; John D. Salamone (Psychopharmacology, 2011)

International symposium on aquaculture, biology and management of commercially important crabs, Shanghai (China), 8–11 November 2009 (ISABMC-2009) - Lewis Le Vay; Colin Shelley; Chaoshu Zeng; Patrick Sorgeloos (Aquaculture International, 2011)

Reproductive factors and risk of contralateral breast cancer by BRCA1 and BRCA2 mutation status: results from the WECARE study - Jenny N. Poynter; Bryan Langholz; Joan Largent; Lene Mellemkjær; Leslie Bernstein; Kathleen E. Malone; Charles F. Lynch; Åke Borg; Patrick Concannon; Sharon N. Teraoka; Shanyan Xue; Anh T. Diep; et al. (Cancer Causes & Control, 2010)

Female philopatry in coastal basins and male dispersion across the North Atlantic in a highly mobile marine species, the sperm whale ( Physeter macrocephalus ) - DANIEL ENGELHAUPT; A. RUS HOELZEL; COLIN NICHOLSON; ALEXANDROS FRANTZIS; SARAH MESNICK; SHANE GERO; HAL WHITEHEAD; LUKE RENDELL; PATRICK MILLER; RENAUD DE STEFANIS; ANA CAÑADAS; SABINA AIROLDI; et al. (Molecular Ecology, 2009)
The mechanisms that determine population structure in highly mobile marine species are poorly understood, but useful towards understanding the evolution of diversity, and essential for effective conservation and management. In this study, we compare putative sperm whale populations located in the Gulf of Mexico, western North Atlantic, Mediterranean Sea and North Sea using mtDNA control region sequence data and 16 polymorphic microsatellite loci. The Gulf of Mexico, western North Atlantic and North Sea populations each possessed similar low levels of haplotype and nucleotide diversity at the mtDNA locus, while the Mediterranean Sea population showed no detectable mtDNA diversity. Mitochondrial DNA results showed significant differentiation between all populations, while microsatellites showed significant differentiation only for comparisons with the Mediterranean Sea, and at a much lower level than seen for mtDNA. Samples from either side of the North Atlantic in coastal waters showed no differentiation for mtDNA, while North Atlantic samples from just outside the Gulf of Mexico (the western North Atlantic sample) were highly differentiated from samples within the Gulf at this locus. Our analyses indicate a previously unknown fidelity of females to coastal basins either side of the North Atlantic, and suggest the movement of males among these populations for breeding.

Physiological responses of two contrasting desert plant species to precipitation variability are differentially regulated by soil moisture and nitrogen dynamics - LISA D. PATRICK; KIONA OGLE; COLIN W. BELL; JOHN ZAK; DAVID TISSUE (Global Change Biology, 2009)
Alterations in global and regional precipitation patterns are expected to affect plant and ecosystem productivity, especially in water‐limited ecosystems. This study examined the effects of natural and supplemental (25% increase) seasonal precipitation on a sotol grassland ecosystem in Big Bend National Park in the Chihuahuan Desert. Physiological responses – leaf photosynthesis at saturating light ( A sat ), stomatal conductance ( g s ), and leaf nitrogen [N] – of two species differing in their life form and physiological strategies ( Dasylirion leiophyllum , a C 3 shrub; Bouteloua curtipendula , a C 4 grass) were measured over 3 years (2004–2006) that differed greatly in their annual and seasonal precipitation patterns (2004: wet, 2005: average, 2006: dry). Precipitation inputs are likely to affect leaf‐level physiology through the direct effects of altered soil water and soil nitrogen. Thus, the effects of precipitation, watering treatment, soil moisture, and nitrogen were quantified via multivariate hierarchical Bayesian models that explicitly linked the leaf and soil responses. The two species differed in their physiological responses to precipitation and were differentially controlled by soil water vs. soil nitrogen. In the relatively deeply rooted C 3 shrub, D. leiophyllum, A sat was highest in moist periods and was primarily regulated by deep (16–30 cm) soil water. In the shallow‐rooted C 4 grass, B. curtipendula, A sat was only coupled to leaf [N], both of which increased in dry periods when soil [N] was highest. Supplemental watering during the wet year generally decreased A sat and leaf [N] in D. leiophyllum , perhaps due to nutrient limitation, and physiological responses in this species were influenced by the cumulative effects of 5 years of supplemental watering. Both species are common in this ecosystem and responded strongly, yet differently, to soil moisture and nitrogen, suggesting that changes in the timing and magnitude of precipitation may have consequences for plant carbon gain, with the potential to alter community composition.

Energetic metabolism during acute stretch-related atrial fibrillation - Jérôme Kalifa; Jean-Michel Maixent; Thierry Chalvidan; Christiane Dalmasso; David Colin; Dragos Cozma; Pierre Laurent; Jean-Claude Deharo; Pierre Djiane; Patrick Cozzone; Monique Bernard (Molecular and Cellular Biochemistry, 2008)

A Global Baseline for Spawning Aggregations of Reef Fishes - YVONNE SADOVY DE MITCHESON; ANDREW CORNISH; MICHAEL DOMEIER; PATRICK L. COLIN; MARTIN RUSSELL; KENYON C. LINDEMAN (Conservation Biology, 2008)
Species that periodically and predictably congregate on land or in the sea can be extremely vulnerable to overexploitation. Many coral reef fishes form spawning aggregations that are increasingly the target of fishing. Although serious declines are well known for a few species, the extent of this behavior among fishes and the impacts of aggregation fishing are not appreciated widely. To profile aggregating species globally, establish a baseline for future work, and strengthen the case for protection, we (as members of the Society for the Conservation of Reef Fish Aggregations) developed a global database on the occurrence, history, and management of spawning aggregations. We complemented the database with information from interviews with over 300 fishers in Asia and the western Pacific. Sixty‐seven species, mainly commercial, in 9 families aggregate to spawn in the 29 countries or territories considered in the database. Ninety percent of aggregation records were from reef pass channels, promontories, and outer reef‐slope drop‐offs. Multispecies aggregation sites were common, and spawning seasons of most species typically lasted Epinephelus striatus ), has undergone substantial declines in aggregations throughout its range and is now considered threatened. Our findings have important conservation and management implications for aggregating species given that exploitation pressures on them are increasing, there is little effective management, and 79% of those aggregations sufficiently well documented were reported to be in decline. Nonetheless, a few success stories demonstrate the benefits of aggregation management. A major shift in perspective on spawning aggregations of reef fish, from being seen as opportunities for exploitation to acknowledging them as important life‐history phenomena in need of management, is urgently needed.

Environments during the Kaihinu Interglacial and Otira Glaciation, coastal north Westland, New Zealand - Neville Moar; R. Patrick Suggate; Colin Burrows (New Zealand Journal of Botany, 2008)
Shoreline gravel of a 47 m raised beach 15 km north of Greymouth, north‐west South Island, is overlain by 6 m of lagoonal deposits, beginning with fine organic silts from which pollen records the replacement of an early podocarp‐hardwood forest by Nothofagus‐ podocarp and then by Nothofagus forest. Plant macro‐remains, including Dacrydium cupressinum (rimu), Nothofagus menziesii (silver beech), N. truncata (red beech), and N. solandri var. cliffortioides (mountain beech), clarify the nature of these forests. Radiocarbon dates >50 000 14 C yr BP and comparison with other north Westland sequences lead to correlation with the early Kaihinu (Last) Interglacial, and assignment to MIS5e and 5d. Locally overlying are 12 m of interbedded slope deposits and alluvial gravel, together with seven organic silt layers (Bed A down to Bed G). Leaves of Nothofagus menziesii were recovered from Bed G and N. solandri var. cliffortioides from higher layers. Bed B shows a significant Poaceae maximum. Radiocarbon dates from Beds G and E are 42700 ± 1300 and 22280 ± 150 14 C yr BP, respectively. The sequence represents much of the Otira (Last) Glaciation, MIS3 and MIS2. The persistence of trees and shrubs at this coastal site is consistent with the inference of closed canopy forest from a site near Westport, but contrasts with the dominance of Poaceae and Cyperaceae at previously studied inland Otira Glaciation sites.

Clinical and molecular genetic features of ARC syndrome - Paul Gissen; Louise Tee; Colin A. Johnson; Emmanuelle Genin; Almuth Caliebe; David Chitayat; Carol Clericuzio; Jonas Denecke; Maja Di Rocco; Björn Fischler; David FitzPatrick; Angeles García-Cazorla; et al. (Human Genetics, 2006)

The RET Mutation E768D Confers a Late-onset Familial Medullary Thyroid Carcinoma – Only Phenotype with Incomplete Penetrance: Implications for Screening and Management of Carrier Status - Tabib Dabir; Steven J. Hunter; Colin F. J. Russell; Damien McCall; Patrick J. Morrison (Familial Cancer, 2006)

Comparison of Belowground Biomass in C3- and C4-Dominated Mixed Communities in a Chesapeake Bay Brackish Marsh - Colin J. Saunders; J. Patrick Megonigal; James F. Reynolds (Plant and Soil, 2006)

Spatial Epidemiology of Caribbean Yellow Band Syndrome in Montastrea spp. Coral in the Eastern Yucatan, Mexico - Janet E. Foley; Susanne H. Sokolow; Evan Girvetz; Colin W. Foley; Patrick Foley (Hydrobiologia, 2005)

Linkage of prostate cancer susceptibility loci to chromosome 1 - Jianfeng Xu; Siqun L. Zheng; Bao-li Chang; Jeffrey R. Smith; John D. Carpten; O. Colin Stine; Sarah D. Isaacs; Kathy E. Wiley; Lauren Henning; Charles Ewing; Piroska Bujnovszky; Eugene R. Bleeker; et al. (Human Genetics, 2001)

Expression and chromosomal localization of the Requiem gene - Theodore G. Gabig; Colin D. Crean; Alison Klenk; Haiyan Long; Neal G. Copeland; Debra J. Gilbert; Nancy A. Jenkins; Danielle Quincey; Fabienne Parente; Françoise Lespinasse; Georges F. Carle; Patrick Gaudray; et al. (Mammalian Genome, 1998)

Scale-up of Adhesive Transdermal Drug Delivery Systems - Glenn A. Van Buskirk; Mario A. González; Vinod P. Shah; Scott Barnhardt; Colin Barrett; Stephen Berge; Gary Cleary; Keith Chan; Gordon Flynn; Thomas Foster; Robert Gale; Raymond Garrison; et al. (Pharmaceutical Research, 1997)